2022
DOI: 10.3390/jcm11092639
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Early Anthropometric, Lipid and Liver Changes after Direct-Acting Antiviral Therapy in PLWHIV with HCV Co-Infection

Abstract: Treatment with interferon-free direct-acting antivirals (DAA) has become the gold standard in chronic hepatitis C virus (HCV) infection. Nevertheless, little research about the metabolic impact of achieving sustained virological response (SVR) is available in HCV/HIV co-infected patients. This research aimed to evaluate early anthropometric, lipid and liver parameters changes after achieving SVR 12 weeks after treatment (SVR12). A real-life retrospective descriptive before-after study assessed 128 DAA treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…We did not find any significant increases in LDL among VLWH who had advanced liver fibrosis and were on a protease inhibitor. Our finding differs from that of Spaziante et al , and Ferra-Murcia, et al , where participants who were on protease inhibitors (atazanavir and darunavir) in LDL and total cholesterol, respectively [14,15]. NRTIs are still used often as many of the INSTI-based fixed-dose ART combinations use NRTI backbones; however, the threshold for initiating statin therapy may need to be lower after SVR to offset the potential CVD risk exacerbated by abacavir.…”
Section: Discussioncontrasting
confidence: 90%
“…We did not find any significant increases in LDL among VLWH who had advanced liver fibrosis and were on a protease inhibitor. Our finding differs from that of Spaziante et al , and Ferra-Murcia, et al , where participants who were on protease inhibitors (atazanavir and darunavir) in LDL and total cholesterol, respectively [14,15]. NRTIs are still used often as many of the INSTI-based fixed-dose ART combinations use NRTI backbones; however, the threshold for initiating statin therapy may need to be lower after SVR to offset the potential CVD risk exacerbated by abacavir.…”
Section: Discussioncontrasting
confidence: 90%
“…Specifically, we observed that age and AFP levels were associated with short-term improvement in liver fibrosis. Feng et al developed a non-invasive index for predicting significant fibrosis, which included AFP with good predictive performance [25] . Both age and elevated AFP are associated with some biological processes such as inflammation, injury, and regeneration, which in turn influence the course of fibrosis.…”
Section: Discussionmentioning
confidence: 99%